"Loose production but great cause!!": a response to the 2019 Rhetoric Society of America Project in Power, Place, and Publics at the University of Nevada, Reno. Issue 2 (2nd April 2020) - Running Wolf, Myrton W.
ABSTRACT: The 2019 Rhetoric Society of America Project in Power, Place, and Publics at the University of Nevada, Reno is a nice case study of how interactions between the academy and American Indian tribes demonstrate the persistent challenges of bridging our nation's entrenched cultural and racial divisions. The unspoken tensions between our tribal communities and our country's corporate/government/higher education institutions continue to result in individual spokespeople having to account for and speak for the entire vastness of our Native American populations.